2022
DOI: 10.3389/fphar.2022.1063035
|View full text |Cite
|
Sign up to set email alerts
|

Protective potential of hydroxysafflor yellow A in cerebral ischemia and reperfusion injury: An overview of evidence from experimental studies

Abstract: Ischemic stroke, mostly caused by thromboembolic or thrombotic arterial occlusions, is a primary leading cause of death worldwide with high morbidity and disability. Unfortunately, no specific medicine is available for the treatment of cerebral I/R injury due to its limitation of therapeutic window. Hydroxysafflor yellow A, a natural product extracted from Carthamus tinctorius, has been extensively investigated on its pharmacological properties in cerebrovascular diseases. However, review focusing on the benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 96 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Many studies have shown that post-stroke neuroinflammation is an important factor affecting long-term ischemic prognosis. Thus, neuroinflammation has been regarded as a vital pathological process following cerebral ischemia-reperfusion injury ( Yu et al, 2022 ).…”
Section: Pharmacological Mechanisms Of Guhong Injection For Ischemic ...mentioning
confidence: 99%
“…Many studies have shown that post-stroke neuroinflammation is an important factor affecting long-term ischemic prognosis. Thus, neuroinflammation has been regarded as a vital pathological process following cerebral ischemia-reperfusion injury ( Yu et al, 2022 ).…”
Section: Pharmacological Mechanisms Of Guhong Injection For Ischemic ...mentioning
confidence: 99%
“…Study investigating the regulatory effects of the main active components in Honghua Injection on the cerebrovascular disease network concluded that HSYA and Quer were enriched in a cluster, implying the two ingredients may have synergistic protective effects against IS [ 17 ]. HSYA was reported to have protective potential against cerebral ischemia and reperfusion injury through multiple mechanisms [ 18 ]. Quer also showed BBB protective effects in middle cerebral artery occlusion/reperfusion (MCAO/R) rat models [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“… 19 Animal experiments have shown that naodesheng (NDS) improves learning and memory function by inhibiting NF-κB and activation of cAMP/PKA/CREB signaling pathway in amyloid β-treated rats. 20 The main components of NDSP, such as tetramethyl pyrazine, 21 hydroxysafflor yellow A, 22 and puerarin, 23 could promote the recovery of neurological function after stroke. However, the therapeutic effects of NDS on ischemic brain injury have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%